A Clinical Risk Model to Predict Rapidly Progressive Interstitial Lung Disease Incidence in Dermatomyositis - Li, Yimin; Li, Yuhui; Wang, Yuguang; Shi, Lianjie; Lin, Fuan; Zhang, Zongxue; Zhang, Jingli; Liu, Yanying; Liu, Xu; Xu, Fangjingwei; Sun, Xiaolin (Frontiers in Medicine, 2021)
Background: Rapidly progressive interstitial lung disease (RP-ILD) is a fatal complication of dermatomyositis (DM) and clinically amyopathic DM (CADM). The aim of this study was to evaluate risk markers associated with RP-ILD incidence in patients with DM/CADM and to develop a RP-ILD risk prediction (RRP) model. Methods: The clinical records of 229 patients with DM/CADM from Peking University People’s Hospital, and 97 patients from four other independent clinical centers were retrospectively reviewed. Univariate and multivariate logistic regression analyses were performed to identify independent risk factors associated with later RP-ILD incidence to build a risk score model. The concordance index (C-index) and calibration curve were calculated to evaluate the predictive accuracy of the RRP model. Results: We established a multiparametric RRP model based on weighted clinical features including: fever (yes, 5; no, 0), periungual erythema (yes, 6; no, 0), elevated CRP (yes, 5; no, 0), anti-MDA5 antibody (positive, 8; negative, 0) and anti-Ro-52 antibody (positive, 6; negative, 0). Patients were divided into three risk groups according to the RRP total score: low, 0–9; medium, 10–19; high, 20–30. The C-index and calibration curve of the RRP model showed a promising predictive accuracy on the incidence of RP-ILD. Conclusion: The RRP model might promisingly predict the incidence of RP-ILD in DM/CADM patients to guide early individual treatment and further improve the prognosis of DM/CADM patients.